Racial/ethnic and socio‐economic biases in child maltreatment severity assessment in Spanish child protection services caseworkers. Issue 2 (9th February 2016) - Arruabarrena, Ignacia; de Paúl, Joaquín; Indias, Silvia; García, Mikel
Abstract: Evidence from several countries has shown the over‐representation of racial/ethnic minority groups in child protection services (CPS). The objective of the present study was to explore whether racial/ethnic and socio‐economic biases influence Spanish CPS caseworkers' judgements of the severity of child maltreatment. Moreover, the study attempted to explore the influence on these judgements of the use of structured instruments and professional experience. Two case vignettes of child maltreatment were presented to 405 CPS caseworkers and 169 students of social work and psychology. Family ethnic origin and income were manipulated in the vignettes. The findings showed no statistical evidence of biases related to family ethnic origin or socio‐economic status (SES) in Spanish CPS caseworkers' judgements of maltreatment severity. Biases related to family SES were found for students for the vignettes of physical abuse. CPS caseworkers and students who did not use a structured instrument to assess maltreatment severity tended to underestimate the severity for the vignettes of parental incapacity to control child/adolescent behaviour and to overestimate it for the vignettes of physical abuse. CPS caseworkers who used a structured instrument showed higher percentages of accuracy and inter‐rater agreement, supporting the relevance of structured tools in reducing potential caseworkers' biases.